SYSTEMS AND METHODS FOR GENERATING DATASETS FOR MODEL RETRAINING - JEONG, Hyunsoo; DWIVEDI, Anand (2024)
A computer system is provided and programmed to assemble a plurality of synthetic datasets and blend those synthetic datasets into a synthesized dataset. An evaluation is then performed to determine whether an existing model should be associated with the synthesized dataset or a new model should be trained from an existing model using the synthesized dataset.